Pengenalan Etika Bisnis Sebagai Upaya Menyiapkan Generasi Muda (Gen Z) Yang Siap Masuk Dunia Industri Kerja - Wulandari, Dwiwahjuni; Ferisanti, Ferisanti (Joong-Ki : Jurnal Pengabdian Masyarakat, 2024)
The emergence of a new generation often referred to as Gen Z, those who were born in the era of 1995 - 2012 began to enter the industrial workforce. It is important for this generation to understand the concept of business ethics as a whole, so that when they take a role in the world of work, they can behave correctly according to the norms regulated in business ethics. Especially considering that this generation, whether we like it or not, is realized together in character is very different from the previous generation. Gen Z is a generation that from birth has received very intensive exposure to technology. This forms a mindset that tends to be egocentric and easily discouraged. Therefore, a correct understanding of business ethics is expected to bridge the gap that is very likely to occur with previous generations in the world of work.